Effectiveness of acupuncture for anxiety and depression in irritable bowel syndrome: A protocol for systematic review and meta-analysis - Li, Huaiyu (Medicine (Baltimore), 2021)
BACKGROUND: Irritable bowel syndrome (IBS) is the most commonly gastrointestinal diseases. The Rome Foundation's global study on 33 countries shows the total prevalence of IBS under the Rome IV Diagnostic Criteria was 3.8%. It is well established that people with IBS have higher levels of anxiety and depression. The impact of the acupuncture associated with anxiety and depression has been widely studied in Western countries. Acupuncture may be a promising choice for the treatment of anxiety and depression in IBS. METHODS: RCTs of acupuncture for depression and anxiety in IBS will be searched in the relevant database, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Biomedical Literature Database (CBM), and Chinese Scientific Journal Database (VIP database). The studies of electronic searches will be exported to EndNote V.9.1 software. We will run meta-analyses using the Review Manager (RevMan) V.5.3 software. Any disagreement will be solved in consultation with a third reviewer. RESULTS: Our study aims to explore the efficacy of acupuncture for depression and anxiety in IBS and to provide up-to-date evidence for clinical of IBS. CONCLUSION: This study will perform a comprehensive systematic review and meta-analysis on the efficacy of acupuncture for depression and anxiety in IBS, making up for the lack of relevant evidence of the clinical use of acupuncture. INPLASY REGISTRATION NUMBER: INPLASY 202120014.